Biomechanical response to systematic changes in impact interface cushioning properties while performing a tennis-specific movement - Stiles, V.; Dixon, S. (Journal of Sports Sciences, 2007)
It is currently not known whether human responses across typical sports surfaces are dependent on cushioning or frictional properties of the interface. The present study assessed systematic changes in surface cushioning (baseline acrylic, rubber, thin foam, and thick foam) as participants performed tennis running forehand foot plants wearing a basic neutral shoe (plimsolls). It was hypothesized that systematic decreases in peak rates of loading, heel pressures, and perceived hardness would be yielded as surface cushioning increased (impact test device). A common acrylic top surface provided consistent frictional properties across surfaces. Kinetics (AMTI, 960 Hz and Footscan Pressure Insoles, 500 Hz), kinematics (Peak MOTUS, 120 Hz), and cushioning perception were assessed. Peak and mean loading rates of vertical ground reaction force, peak horizontal force, peak heel pressure, and rates of loading demonstrated significant correlations (P < 0.05) with the participants' perceived levels of cushioning and matched mechanical rankings of surface cushioning. In contrast, peak impact force was lowest on the least cushioned surface. Kinematic responses were not significantly different between surfaces. Present evidence supports ''peak rate of loading'' as a more suitable indicator of surface cushioning than peak impact force. Although cautionary, biomechanical support is also provided for mechanical methods of surface cushioning assessment.